Acid induced destabilization of emulsions prepared with sodium caseinate–epigallocatechin-gallate complexes. (December 2016) - Sabouri, Somayeh; Corredig, Milena
Abstract: Complexes of epigallocatechin-gallate (EGCG) and sodium caseinate adsorbed at the interface of oil in water emulsions may affect the stability and processing functionality of the emulsion droplets. The objective of this work was to determine the effect of presence of these complexes at the oil–water interface on the colloidal behaviour of the emulsion during acidification. Emulsions were prepared with 7% soybean oil, 0.35% sodium caseinate, and 0, 2, or 6 mg/ml EGCG. The acid induced aggregation was studied in the presence of high methoxyl pectin at concentration ranging from 0 to 0.45%. In situ light scattering measurements demonstrated that the presence of EGCG at the interface lowered the pH of destabilization of sodium caseinate covered droplets, and caused changes in the processing properties of the emulsions. The complex formed at the interface also reduced the electroadsorption of high metoxyl pectin, and caused differences in the emulsions microstructure at acid pH. In spite of the widespread utilization of EGCG as a bioactive ingredients in emulsion dairy drinks, this work illustrates how the presence of protein-EGCG complexes at the interface affect the processing behaviour of emulsion droplets. Graphical abstract: Highlights: EGCG forms complexes at the oil water interface with sodium caseinate. Complexes do not affect the emulsion droplets charge during acidification. The pH of shifts to a lower pH in the presence of EGCG. Less coalescence and flocculation occurs when complexes are present. The adsorption of high methoxyl pectin during acidification occurred at a lower pH with EGCG.